Forecasting Investment Needs in South Africa's Electricity and Telecommunications Sectors - Bogetić, Željko; Fedderke, Johannes W. (World Bank, Washington, DC, 2012)
The authors use a panel-data set for the period 1980-2002 to estimate demand for electricity and telecommunications services and project investment needs in South Africa through 2010 for two growth scenarios. Projections of average annual investment needs in electricity and telecommunications for the current growth scenario (3.6 percent a year) are of the order of 0.2 percent and 0.75 percent of GDP, respectively. An alternative, accelerated growth scenario (6 percent a year) implies approximate doubling of investment needs in these sectors.